ETHNOMATHEMATICS DAN PERMAINAN TRADISIONAL DALAM PENDIDIKAN MATEMATIKA - Elfi Rahmadhani (IKIP Siliwangi, 2022)
Ethnomathematics is a field that discusses mathematics which is associated with culture. Among them are traditional games, traditional ceremonial equipment, numbers, and other cultures. This research is qualitative research with a meta-analysis method that uses the results of both international and national previous studies that discuss the use of ethnomathematics in mathematics learning in the 2000-2020 period. The purpose of this study is to analyze each article obtained about the use and influence of ethnomathematics and traditional games in mathematics education. The research results used in this study consisted of 161 articles from 250 articles obtained. The results of the analysis show that ethnomathematics and traditional games have a significant influence on students' mathematical abilities. In general, mathematical material that can be found based on the results of the analysis is geometry, numbers, and algebra. The use of traditional games to instill concepts in students has an impact on students' mathematical understanding. Besides being able to help understand mathematical concepts, character values are also found in traditional games and cultures from certain areas, such as the values of honesty, cooperation, self-confidence, empathy, and others.